Alemtuzumab consolidation in chronic lymphocytic leukaemia: a phase I/II multicentre trial. (1st December 2016) - Al‐Sawaf, Othman; Fischer, Kirsten; Herling, Carmen D.; Ritgen, Matthias; Böttcher, Sebastian; Bahlo, Jasmin; Elter, Thomas; Stilgenbauer, Stephan; Eichhorst, Barbara F.; Busch, Raymonde; Elberskirch, Ute; Abenhardt, Wolfgang; et al.
Abstract: Objective: Despite high rates of long‐lasting remissions in patients with chronic lymphocytic leukaemia (CLL) treated with chemoimmunotherapy, none of the current therapeutic approaches is curative with the exception of allogeneic transplantation. One strategy to extend progression‐free survival and long‐term survival might be the establishment of consolidation therapies. Methods: In this trial, patients with complete or partial second remission after fludarabine‐based treatment received consolidation therapy with alemtuzumab. The aim of this phase I/II trial was to determine the maximal tolerable dose (MTD) of alemtuzumab consolidation and to evaluate safety and efficacy in patients who responded to second‐line fludarabine‐based treatment. Thirteen patients in complete (CR) or partial remission (PR) received alemtuzumab dose escalation starting with 10 mg intravenously (iv) once weekly for 8 wk and increasing in 10‐mg intervals per dose level. Results: The main dose‐limiting toxicities (DLTs) were infectious complications, and the MTD was determined at 10 mg. After alemtuzumab consolidation, seven of 13 patients (53%) were in CR, and four of these patients (30.7%) achieved minimal residual disease (MRD) negativity (<1 × 10E‐4). At a median follow‐up of 71.5 months, four patients were progression‐free, with a median progression‐free survival (PFS) of 28.5 months after the end of second‐line treatment. Conclusion: The results provide a safe and efficient schedule with weekly intravenous application of 10 mg of alemtuzumab as a consolidation regime in patients with CLL.